2017
DOI: 10.1002/ijc.30664
|View full text |Cite
|
Sign up to set email alerts
|

A histone deacetylase inhibitor enhances expression of genes inhibiting Wnt pathway and augments activity of DNA demethylation reagent against nonsmall-cell lung cancer

Abstract: Development of new inhibitors targeting histone deacetylases (HDACs) with improved efficacy for solid tumor therapy is urgently needed. Here, we report the development of a novel HDAC inhibitor TMU-35435 and verify it as a single agent and in combination treatment with DNA demethylation reagent 5-aza-2'-deoxycytidine (5-aza-dC) in lung cancer preclinical models. TMU-35435 exerted cancer-specific cytotoxicity via mitochondria-mediated apoptosis. Expression microarrays revealed a unique TMU-35435-induced gene ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 35 publications
1
13
0
1
Order By: Relevance
“…In lung cancer cells that were treated with a novel HDAC inhibitor TMU-35435, microarray analysis identified cell proliferation and the Wnt signaling pathway as enriched biological processes [52]. In H460 human lung carcinoma cells that were treated with butyrate, microarray analysis revealed 32 genes with greater than two-fold increase and 66 genes less than one-third expression level as compared with the untreated cells.…”
Section: Transcriptomic Effects Of Hdismentioning
confidence: 99%
“…In lung cancer cells that were treated with a novel HDAC inhibitor TMU-35435, microarray analysis identified cell proliferation and the Wnt signaling pathway as enriched biological processes [52]. In H460 human lung carcinoma cells that were treated with butyrate, microarray analysis revealed 32 genes with greater than two-fold increase and 66 genes less than one-third expression level as compared with the untreated cells.…”
Section: Transcriptomic Effects Of Hdismentioning
confidence: 99%
“…The results showed significant stimulation of hOCT1 expression ( Figure 5B). Because it has been reported that the effect of DAC can be enhanced by histone deacetylase inhibitors (Shieh et al, 2017), HepG2 and HuH7 cells were exposed to 5 mM sodium butyrate, a previously evaluated non-toxic concentration (data not shown), for 24 h, and the hOCT1 expression was measured. Although sodium butyrate alone stimulated hOCT1 expression, the combination with DAC did not further increase hOCT1 expression (data not shown).…”
Section: Role Of Dna Methylationmentioning
confidence: 99%
“…TMU-35435 which functions as a histone deacetylase (HDAC) inhibitor successfully induced G 2 /M stage arrest of four different NSCLC cell lines while leaving non-cancerous lung cells intact. Its mode of action was through upregulation of several genes encoding for Wnt inhibitors, possibly by catalyzing the presence of activating acety-lation histone marks [111]. The antitumor effects of norcantharidin consisted of decreased methylation of WIF-1 gene promoters and increased expression of SFRP1.…”
Section: Pharmacological Targetingmentioning
confidence: 99%